Characterization of injection molding parameter using flow simulation and Taguchi method / [cakera padat] - 434423 Keh, Teng Yang (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Mechanical)) - Universiti Teknologi Malaysia, 2001